2018
DOI: 10.1515/helm-2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

Complementary effect of Capparis spinosa L. and silymarin with/without praziquantel on mice experimentally infected with Schistosoma mansoni

Abstract: SummarySchistosomiasis remains to be the most common fi brotic disease resulting from infl ammation and deposition of scar tissue around trapped parasitic eggs in the liver. Though chemotherapy eradicates matured worms effi ciently and prevents the accumulation of schistosome eggs, fewer effective drugs are directed to reverse the present hepatic fi brosis. Therefore, treatment targeting hepatic fi brosis associated with schistosomiasis remains a challenging proposition. The present study was designed to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…(2019 investigated the acute toxicity effect of polyphenolic extract of the plant leaves and the extract was nontoxic at doses up to 100 mg/kg b.w (Oudah hamam et al, 2019). The hydroalcoholic extract of Caper fruits in rats showed an LD 50 value of 400 mg/kg supporting results encountered by El-Hawary et al (2018) who demonstrated no mortality in rats within 24 h of pretreatment with Caper methanol extract at The level of liver MDA significantly declined while the GSH activity was significantly elevated after treatment with the extract at 200 and 400 mg/kg while the group treated with TAA showed higher levels of MDA and lower levels of GSH.…”
Section: Toxicity Studiessupporting
confidence: 81%
“…(2019 investigated the acute toxicity effect of polyphenolic extract of the plant leaves and the extract was nontoxic at doses up to 100 mg/kg b.w (Oudah hamam et al, 2019). The hydroalcoholic extract of Caper fruits in rats showed an LD 50 value of 400 mg/kg supporting results encountered by El-Hawary et al (2018) who demonstrated no mortality in rats within 24 h of pretreatment with Caper methanol extract at The level of liver MDA significantly declined while the GSH activity was significantly elevated after treatment with the extract at 200 and 400 mg/kg while the group treated with TAA showed higher levels of MDA and lower levels of GSH.…”
Section: Toxicity Studiessupporting
confidence: 81%
“…The poisonous compounds are concentrated in the vegetable parts, floral buds, flowers, peel and seeds (47). The LD50 of Capparis spinosa fruit extract was reported to be greater than 4000 mg/kg in rats (48).…”
Section: Capparis Spinosa Lmentioning
confidence: 99%
“…Other studies have showed limited activity of gram-positive and gram-negative bacteria (Helicobacter pylori, Escherichia coli, Mycobacterium tuberculosis and Bacillus cereus) by C. spinosa [12,13]. In addition, total polyphenols of C. spinosa alone or in together with praziquantel exhibited schistosomicidal and hepatoprotective effects in mice infected with Schistosoma mansoni [14]. Therefore, the present study was designed to evaluate the effect of hydroalcoholic extracts of C. spinosa leaves and fruits on G. lamblia cysts in vitro.…”
Section: Introductionmentioning
confidence: 94%